Dental drive through model of care to reduce caries incidence - Ramini Shankumar; Parul Marwaha (Elsevier, 2021)
Aim or purpose: An increase in number of people seeking emergency care due to inability to access dental services for general care was seen during COVID-19. This drive through model was developed to screen, educate and prioritise, based on individual risks, patients who were otherwise unable to get dental care due to COVID-19 restrictions. Methods: On World Oral Health Day, 2021 dental examinations were conducted for patients while they drove through an existing COVID-19 screening clinic. The ICDAS-II index (International Caries Detection and Assessment System), score two to six, was used for caries assessment and management. Patients were categorised into three groups based on number of decayed teeth (less than three, three to six or more than six). The management criteria was based on the ICDAS score of teeth under each of the three categories. Results: A total of 247 patients were screened and educated on the day. 102 patients with ICDAS score two to four were given education and preventative treatment appointment. While 118 patients with ICDAS score five or six were identified to be at risk of dental emergency in the near future and were booked in for emergency or general treatment. Another 27 patient were given clinical priority based on their periodontal or denture related needs. Patient survey revealed a high satisfaction rate of 92%. Conclusions: This public health initiative was a great success in providing dental care to the patients during these unprecedented times who would not have had any care otherwise due to COVID-19 restrictions.